Therapeutic potential of a 2, 2'-bipyridine-based vanadium(IV) complex on HepG2 cells: cytotoxic effects and molecular targeting. Issue 1 (31st December 2023) - El-Shafey, Eman Salah; Elsherbiny, Eslam Samy
ABSTRACT: Vanadium complexes as non-platinum metallic drugs have gained considerable importance as an appropriate candidate for cancer treatment The study aimed to investigate the patent therapeutic activity of [VO (bpy)2 Cl] Cl.H2 O complex in HCC cells: Viability of cells was detected by MTT method. Flow cytometry detected cell cycle, apoptosis Microtubule-associated protein 1A/1B-light chain 3 (LC3) and acid vascular organelles (AVOs) levels. ELISA was used for caspase-3 levels. AVOs was detected by fluorescence microscope. Real time PCR was assessed for Cyclin D1 gene expression HepG2 cellular growth was inhibited after treatment. Triggering of apoptosis was indicated by elevation of cells in sub G0, apoptotic phases, and the increase in caspase-3 levels. Stimulation of autophagy was reflected by the propagation of cells in G0/G1 phase, the raising of AVOs and elevation of LC3 levels. Suppression of Cyclin D1 gene expression was detected. [VO (bpy)2 Cl] Cl.H2 O complex could be taken into account as a vanadium-based drug that mediated its antitumor activity on HCC cells.